Towards a Pilot Plan for Preventive Conservation based on the Maintenance Campaign of San Roque - Achig Balarezo, María Cecilia (Universidad de Cuenca, 2016)
The need to have a Plan of Preventive Conservation, it is essential with regard to the processes of conservation of the heritage. This article presents a methodology developed by the project "Ciudad Patrimonio Mundial", which contributes to the development of a pilot Plan for preventive conservation, developed bearing in mind the proposal made by the ICOMOS for study of damage and consists of the following aspects: "anamnesis, diagnosis, treatment and control". (ICOMOS: 2003).In this way were determined four-phase plan, which have been implemented according to the experiences of the campaigns of preventive conservation (maintenance, in this specific case) applied in Susudel (December - 2011 and January 2013) and from the campaign of maintenance applied to heritage buildings of San Roque. At the end they will be presented the results of the campaign, from which general strategies for the development of a pilot Plan for preventive conservation in San Roque will be developed, which is aimed at the conservation of the heritage buildings in this neighborhood of Cuenca, in order to apply this methodology in sectors strategically chosen of this World Heritage City.Keywords: Preventive conservation, heritage conservation, maintenance, monitoring, maintenance campaign, management plan, community participation.